Artificial intelligence in clinical imaging: a health system approach. Issue 1 (January 2020) - Gilbert, F.J.; Smye, S.W.; Schönlieb, C.-B.
Abstract : The development and application of artificial intelligence (AI) to radiology requires an approach that encompasses a health system. The UK government and National Health Service (NHS) are creating an ecosystem to facilitate academic/industrial partnerships aimed at accelerating the creation of relevant and robust AI tools, which will improve the development and delivery of healthcare imaging. A series of recent initiatives are described, which will drive the development and adoption of AI in clinical imaging.